On the noise reduction mechanisms of porous aerofoil leading edges. (27th October 2020) - Chaitanya, Paruchuri; Joseph, Phillip; Chong, Tze Pei; Priddin, Matthew; Ayton, Lorna
Abstract: This paper is predominantly an experimental study into the reduction of turbulence - aerofoil interaction noise by the introduction of aerofoil porosity. In this paper we study three scenarios applied to flat plates: (a) when the flat plate is fully porous, (b) when the flat plate is partially porous from the leading edge and (c) when porosity is introduced downstream of the leading edge. This paper shows that the noise reduction spectra collapse when plotted against non-dimensional frequency fl / U, where l is the length of porous section and U is the flow velocity. Narrow band measurements on a partially porous aerofoil have shown that its noise reduction spectra is characterised by a number of narrow peaks. This paper proposes two main mechanisms for explaining this behaviour. The noise reduction mechanisms are validated against noise reductions measured on a realistic aerofoil at relatively low angles of attack. One of the key findings of this paper is that, by using only a single row of holes downstream of the aerofoil leading edge one can obtain significant levels of noise reduction. This use of downstream porosity is specifically shown to be capable of providing low-frequency noise reductions without increasing the radiated noise at higher frequencies.